2019
DOI: 10.1111/jcmm.14671
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteases and TIMPs as prognostic biomarkers in breast cancer patients treated with radiotherapy: A pilot study

Abstract: Breast cancer (BC) is the most common tumour in women and one of the most important causes of cancer death worldwide. Radiation therapy (RT) is widely used for BC treatment. Some proteins have been identified as prognostic factors for BC (Ki67, p53, E‐cadherin, HER2). In the last years, it has been shown that variations in the expression of MMPs and TIMPs may contribute to the development of BC. The aim of this pilot work was to study the effects of RT on different MMPs (‐1, ‐2, ‐3, ‐7, ‐8, ‐9, ‐10, ‐12 and ‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…On the other hand, MMP-2 and MMP-9 proteolytic activity was increased with increasing radiation doses, suggesting that matrix degradation does continue to occur. The elevation of MMP activity after radiation exposure has already been extensively reported in patients receiving radiotherapy for various types of cancer, including breast cancer and malignant gliomas (40)(41)(42). Our findings are therefore in line with other studies that examined the effects of radiation on MMP function.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, MMP-2 and MMP-9 proteolytic activity was increased with increasing radiation doses, suggesting that matrix degradation does continue to occur. The elevation of MMP activity after radiation exposure has already been extensively reported in patients receiving radiotherapy for various types of cancer, including breast cancer and malignant gliomas (40)(41)(42). Our findings are therefore in line with other studies that examined the effects of radiation on MMP function.…”
Section: Discussionsupporting
confidence: 91%
“…The balance between MMPs and their tissue inhibitors (TIMPs) plays a crucial role in cancer progression and metastasis [23]. Our previous work has shown the involvement of MMP-3, MMP-9, TIMP-3, and TIMP-4 in response to radiotherapy in breast cancer patients, suggesting their utility as potential prognostic and predictive biomarkers for this pathology [24]. In breast cancer, several strategies for the development of inhibitors with therapeutic potential targeting the MMPs were discussed by Radisky et al [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Ets-1, an important transcription factor for regulating the invasion and metastasis of tumors, has a binding site on the MMP9 promoter (29), explaining the role of MMP9 in promoting the invasion of breast cancer. A recent study reported that MMP1-induced brain metastasis of breast cancer is related to the downregulation of non-coding RNAMiR-202-3p expression in brain metastases (30). While investigating treatments for breast cancer, Olivares-Urbano et al found that serum levels of tissue inhibitors of MMP1 and MMP3 (TIMP-1 and TIMP-3) were reduced following radiotherapy and inversely proportional to the 30-minute treatment time, which provided a new basis for predicting radiotherapy toxicity.…”
Section: Discussionmentioning
confidence: 99%